Prospects of using the UFMC technology In 5g / Imt-2020 networks - Ahmed Sabri Ghazi Behadili; Emad Jadeen Abdualsada Alshebaney; Aqeel Lateef Khudhair attaby (Institute of Advanced Engineering and Science, 2019)
The article considers the technology of frequency multiplexing with universal filtering UFMC, planned to be introduced in the fifth generation of mobile communication networks, which allows maximizing the rate of decay of the side lobes of the multifrequency signal spectrum that cause out-of-band emissions. As a method of investigation, a computational experiment was chosen. The parameters of the OFDM and UFMC signals were compared to determine the gain of the UFMC technology in the occupied bandwidth of the signal spectrum, as well as the number of arithmetic operations, required to generate a data symbol compared to the OFDM technology, on the basis of which, conclusions were made about the practical application of UFMC technology in networks mobile communication of the fifth generation. The conducted analysis can help to select the optimal number of sub-channels in groups in order to minimize the amount of computations during the UFMC symbol generation process.